Dunking the dust: innovation diffusion, informality and policy opportunities in a stone crushing cluster, India. Issue 1 (2nd January 2020) - Das, Keshab; Yap, Nonita Tumulak
ABSTRACT: This paper explores the barriers to the diffusion of environmental innovation among informal enterprises with a stone crushing cluster in Odisha as a case study. The huge dust cloud resulting from the crushing process has polluted the air and settled on farmlands and homesteads in the surrounding region. This has been associated with farm productivity decline, road accidents, school drop-outs, out-migration and various ailments. The use of water sprinklers as an environmental innovation has been the major response of the state pollution control authorities. Few have complied. The barriers are examined drawing upon interviews with 50 enterprises and various stakeholders and review of secondary sources. Absence of community pressure in the cluster, pecuniary gains of informality, and dysfunctional institutional arrangements appear to leave businesses with little incentive to reduce their burden on workers' health, the environment and the community. However, experiences in other developing countries suggest there are policy opportunities for overcoming these barriers.